Semantic Broadening of the Word Sudah in the Spoken Use of Bahasa Indonesia in Sumba - Raynesta Mikaela Indri Malo (RETORIKA: Jurnal Ilmu Bahasa, 2020)
This is a descriptive qualitative study which aims at studying the use of the word sudah in the spoken use of Bahasa Indonesia in Sumba. According to Kamus Besar Bahasa Indonesia, sudah is an adverb used mostly to inform that something has already happened or that something has already been done. The position of sudah in phrases or sentences precedes the verb or adjective that it modifies. However, there is a different use of sudah in Sumba, and probably in mostly eastern islands in Indonesia, where this adverb is placed after the verb. The purpose of this research is to study the meaning brought by this new arrangement of sudah. The data was spoken use of Bahasa Indonesia collected through note-taking at campus, houses, and public places (market and stores). The data collected was then analyzed using agih method or meaning-analysis method. There were also 2 informants asked to get information on the function of the new arrangement. The analysis showed that the adverb sudah underwent the semantic or meaning broadening in its use. This study revealed there were 3 new meanings as the result of broadening process, (1) to give order or to ask other people to do something, (2) to invite other people to do something, and (3) to inform that something is about to happen or to be done soon. With these new meanings, the adverb sudah can also function as an adverb to show that something has not happened yet or something has not been done yet, the contrast of what is suggested in the dictionary.